2016
DOI: 10.1177/2158244016654949
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Look at the Experiences of Filipina Correspondence or Internet Brides

Abstract: Studies on women's experiences as correspondence or Internet brides that were conducted used survey instruments, interviews, and other tests created and normed on U.S. populations. This study specifically examined the experiences of Filipina women who have utilized an international dating agency or other venues to meet their husbands. It attempted to phenomenologically extract the essence of this population's experiences as correspondence or Internet brides. Phenomenological analysis was conducted on the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is clear through literature reviews and current research that the men who utilize the broker agencies tend to hold conservative, traditional values, which they expect their wives to share. Some Filipina women interviewed found that the traditional lifestyle expected from their husbands actually helps them stay connected to their own culture, which provides comfort amid the discomfort of moving away from their home country (Demanarig & Acosta, 2016). However other women find this creates unequal power distributions within the marriage, with women feeling unable to express themselves and their own goals (Philippines Women Centre of B.C, 2000, p. 52).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear through literature reviews and current research that the men who utilize the broker agencies tend to hold conservative, traditional values, which they expect their wives to share. Some Filipina women interviewed found that the traditional lifestyle expected from their husbands actually helps them stay connected to their own culture, which provides comfort amid the discomfort of moving away from their home country (Demanarig & Acosta, 2016). However other women find this creates unequal power distributions within the marriage, with women feeling unable to express themselves and their own goals (Philippines Women Centre of B.C, 2000, p. 52).…”
Section: Discussionmentioning
confidence: 99%
“…Another coping mechanism—communication—implies building dialogue between partners to negotiate their family issues and culturally induced differences to support their relationship while avoiding disagreement and conflict (Demanaraj & Acosta, 2016). Regular and effective communication allows interracial couples to develop a “common” language and a shared system of values and beliefs (Choi et al, 2013).…”
Section: Coping Mechanismsmentioning
confidence: 99%
“…This places married women in a position of dependence on their South Korean spouses, reducing their autonomy. There are a number of studies on the mental health problems these women face due to changes in the living environment, lifestyle, and cultural adaptation stress, such as depression and anxiety [10,11]. Studies have repeatedly expressed that female migrants tend to experience more cultural adaptation stress and depression [12][13][14].…”
Section: Introductionmentioning
confidence: 99%